Normed spaces equivalent to inner product spaces and stability of functional equations - Chmieliski, Jacek (Aequationes mathematicae, 2014)
Let be a normed space. If is an equivalent norm coming from an inner product, then the original norm satisfies an approximate parallelogram law. Applying methods and results from the theory of stability of functional equations we study the reverse implication.